Towards research assessment reform for the social sciences and humanities:: progress and insights from the GraspOS Project (Libellarium: journal for research in the field of information and related sciences, 2026)
Purpose. This study focuses on developing research assessment criteria for the Social Sciences and Humanities (SSH) through the GraspOS project. The aim is to reform traditional evaluation methods that rely heavily on bibliometric indicators and to produce recommendations tailored to the SSH community, addressing the limitations of current practices that predominantly emphasise quantitative metrics.Approach/methodology/design. This study presents outcomes from three workshops with participants from various SSH backgrounds. The workshops facilitated discussions on values-driven assessment, output diversity, and the integration of qualitative indicators. The data collected were analysed using the deductive method, with a priori codes established.Findings. The analysis revealed consensus on the need for a more inclusive evaluation framework that recognises diverse outputs beyond traditional journal articles. Participants emphasised the importance of qualitative measures, such as peer review, and proposed using narrative CVs to better reflect individual contributions.Research limitations. The study was conducted within a specific context of the Responsible Research Assessment (RRA) movement and the GraspOS project, which may not fully represent the broader SSH landscape. Generalisation to all SSH disciplines is not possible.Practical implications. The study provides recommendations for formulating generic research assessment criteria as suggested by SSH scholars.Originality value. This work provides valuable insights into developing more equitable and effective assessment practices in academia for the SSH community.
Keywords: open science; research culture; research evaluation; responsible research assesment; social sciences and humanities